Iqbal's ideas for the restoration of Muslim dynamism - Abdul Razak, Mohd Abbas (International Islamic University Malaysia, 2011)
Islam seeks to develop the human minds to a total submission to Allah the Almighty. Through its divine guidance, the Qur’an ushered a large section of the masses in Arabia from the darkness of ignorance into knowledge and enlightenment of their souls. Islam grew from a humble beginning into a mighty civilizational force. Islamic civilization like all other civilizations, started to decline after reaching its pinnacle of success. Ever since the fall of Baghdad in 1258, the Muslim world has been confronted with endless problems in all fields of life. Colonization of Muslim lands by the West had created the knowledge and technological gap between them and their colonizers. Being subjected to colonization, neo-colonization, and now globalization, Muslims are lagging behind other communities of the world. The Muslim minds which once came up with great ideas, discoveries, innovation and inventions, at the moment somehow become less prolific, and experiencing a state of lethargy and malaise. In realizing the great challenges faced by the Muslims in the modern world, this research intends to re-visit Iqbal’s ideas to remedy the awful situations experienced by the Ummah.